The imagination effect when using textual or diagrammatic material to learn a second language. (July 2023) - Ignatova, Olga; Kalyuga, Slava; Sweller, John
The imagination effect occurs when students learn better from imagining concepts and procedures rather than from studying them. Cognitive load theory explains the effect by better use of available working memory resources and increased productive, intrinsic cognitive load. The effect has been found in numerous empirical studies. However, in the majority of studies demonstrating the effect, visual/spatial information has been used: the type of information that is believed to be easy for imagining. The reported two experiments investigated if an imagination effect could be obtained using verbal information in the area of learning a second language. The results indicated that while textual material was expectedly more difficult for learning than diagrammatic material, asking learners to imagine textual material did improve performance. Cognitive load theory has been used as a theoretical framework to interpret the results.